PUBLISHING STATISTICS: INSIGHTS ON DEVELOPMENT AND SOURCE ANALYSIS - RUDŽIONIENĖ, JURGITA (Knygotyra, 2013)
The article aims at presenting some international and Lithuanian publishing statistics insights, following the development of statistical sources and publishing statistics. It does not attempt to present an exhaustive source and publishing statistics development analysis. Instead, the author sought to reveal the Lithuanian situation of publishing statistics as well as international context, following the importance of sources and development trends in publishing statistics. The concept and principles of publishing statistics are discussed, beginnings and development features are presented, publishing statistics sources are identifieed, documents regulating the preparation of publishing statistics as well as international principles and attitudes are analysed in the article. The background of publishing statistics in the Lithuanian state is presented as well as its role and sources (an ongoing annual publication “Lithuanian Publishing Statistics“ (Lietuvos spaudos statistika), prepared by Martynas Mažvydas National Library of Lithuania, and the relevant publications presenting publishing statistics in early periods) are presented. Special attention is drawn to international publishing statistics situation and sources. UNESCO documents “Recommendation concerning the International Standardization of Statistics relating to Book Production and Periodicals”, 1964, “Revised Recommendation concerning the International Standardization of Statistics on the Production and Distribution of Books, Newspapers and Periodicals”, 1985 and the international standard “ISO 9707: 2011 Information and Documentation. Statistics on the Production and Distribution of Books, Newspapers, Periodicals and Electronic Publications” as well as the respective Lithuanian standard “LST ISO 9707: 2011 Informacija ir dokumentavimas. Statistiniai duomenys apie išleistas knygas, laikraščius, periodinius ir elektroninius leidinius bei jų platinimą”, adopted on the basis of this international standard, serves as methodological background and a relevant tool for preparing publishing statistics in Lithuania as well as at international level. The main international statistical sources, such as “Statistical Yearbook UNESCO“ and “Index Translationum“ are analysed. Special attention is given to “Index Translationum“, which is an international bibliography of book translations, created in the year 1932. The main conclusions on the subject are presented in the article. The analysis in question should serve as an impetus for book scientists, publishing and other specialists to focus on publishing statistics as an important field of interest. Some of the aspects of the subject were presented by the author during the international scientific conference “Book and other Media Science: Research, Scientists, Communication“ (October 22–23, 2009, Vilnius University).